2021
DOI: 10.1016/j.ijmecsci.2020.106175
|View full text |Cite
|
Sign up to set email alerts
|

A verified solution of friction factor in compression test based on its sample's shape changes

Abstract: The friction factor is a key input for "barrel compression test " and for a meaningful interpretation of the test data. Despite its widespread use, due to the complexity of the problem, there are very few solutions available for the test, let alone for the friction factor. Extended-Avitzur (EA) model has serious known limitations to calculate the friction factor. To estimate the friction factor more reliably, a closed-form solution of the friction factor has been proposed here. The solution is based on the "Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…A recently developed model for ACT (details could be found in Khoddam, 35 Khoddam et al 36 ) allows the estimation of the test's heterogeneous deformation and the friction factor via its closed-form solution. Based on a single set of the test's barrelling-load-deformation data and the model's closed-form solution, one can estimate the strain and strain rate changes in the sample, instantaneous friction to eventually identify the material's flow response.…”
Section: Axisymmetric Compression Test (Act)mentioning
confidence: 99%
See 2 more Smart Citations
“…A recently developed model for ACT (details could be found in Khoddam, 35 Khoddam et al 36 ) allows the estimation of the test's heterogeneous deformation and the friction factor via its closed-form solution. Based on a single set of the test's barrelling-load-deformation data and the model's closed-form solution, one can estimate the strain and strain rate changes in the sample, instantaneous friction to eventually identify the material's flow response.…”
Section: Axisymmetric Compression Test (Act)mentioning
confidence: 99%
“…86,88 Another approach is to indirectly characterize/measure friction using the barrelled sample geometry, for example, Alexandrov et al, 89 Yao et al, 90 Fan et al, 91 and Solhjoo and Khoddam. 88 Methods to account for friction, excluding the barrelling, with either a fixed Coulomb friction coefficient and mixed sticking-sliding friction, as well as a recently developed method by Khoddam et al 36 are reviewed and discussed in section 6.…”
Section: Known Issues With the Compression Testmentioning
confidence: 99%
See 1 more Smart Citation
“…As the BCT sample deforms, its boundary condition changes via partial migration of the sample’s free surface to the platen-material contact area, that is, foldover . Several unwanted effects, such as friction induced barrelling, 5 heterogeneous deformation and foldover, drive the test into a multiaxial mode. These effects complicate the interpretation and transformation of the test results to the real forming processes and thus eventually invalidate the physical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Khoddam et al 21 proposed an energy-based approach to evaluate closed-form solutions of the test. Khoddam et al 5 utilised a proposed kinematic solution 22 in an energy conservation framework and developed a closed-form solution for friction factor during the test. They found that their identified friction factor is valid before the onset of foldover.…”
Section: Introductionmentioning
confidence: 99%